Integrating Al-Ghazali’s Educational Philosophy: Advancing Transformative Learning in Islamic Schools in the Digital Era - Husin Husin; Abdul Rashid bin Abdul Aziz; Mowafg Masuwd (SYAMIL: Journal of Islamic Education, 2025)
This study examines the importance of integrating Al-Ghazali's legacy into modern Islamic education. This study focusing on the concept of meaningful learning and relevant teaching practices. The research aims to analyze how Al-Ghazali's principles can be applied in today's educational context. The methodology employed is library research, involving a review of various relevant literature and sources. The findings reveal that applying Al-Ghazali's teachings can enhance both academic understanding and character development in students, offering a comprehensive approach to modern education.